Downed woody debris varies with climate and harvesting treatment in Douglas-fir forests of British Columbia, Canada - Roach, Winnifred Jean; Simard, Suzanne W.; Snyder, Eva N. (Frontiers in Forests and Global Change, 2024)
Downed woody debris is important for biodiversity, forest regeneration, and carbon, nutrient, and water cycling, and past studies have examined how the coarse fraction is affected by climate or harvesting. In a field study in Douglas-fir dominated forests, we expand existing knowledge by investigating the interacting effects of climate and harvesting on downed woody debris of all sizes. Across a 900-km long latitudinal gradient in British Columbia, we found that coarse woody debris (CWD, >7.5 cm diameter) in humid climates contained 700% greater carbon stocks, had 500% greater volume, and was more diverse than in arid climates. Pre- and post-harvest, small and fine woody debris comprised a higher proportion of total woody debris carbon stocks in arid than moist climates, especially after clearcutting and seed tree treatments. Harvesting generally decreased total CWD volume, but it was not depleted on any site. Harvesting substantially reduced the volume of large, highly decomposed CWD except at the two most arid sites, and losses of large CWD increased with increasing tree removal. These losses were accompanied by a pulse of fresh, small diameter CWD and SWD which are short-term organic nutrient sources but have less habitat value than larger pieces and contribute to fuel loads. Because CWD was less abundant in arid than humid mature forests, care must be taken on arid sites to avoid its depletion during harvesting, especially clearcutting, where future woody debris inputs will not occur for decades.